Detailed epitope mapping of SARS-CoV-2 nucleoprotein reveals specific immunoresponse in cats and dogs housed with COVID-19 patients. (March 2022) - Colitti, Barbara; Bonfante, Francesco; Grazioli, Santina; Anfossi, Laura; Nogarol, Chiara; Scalas, Daniela; Bertolotti, Luigi; Bortolami, Alessio; Pagliari, Matteo; Pezzoni, Giulia; Moreno, Ana; Lelli, Davide; et al.
Abstract: Since the initial emergence in December 2019, the novel Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has been reported in over 200 countries, representing an unprecedented challenge related to disease control worldwide. In this context, cases of human to animal transmission have been reported, raising concern about the potential role of companion animals in the pandemic and stressing the need for reliable animal testing. In the study, a detailed epitope mapping of SARS-CoV-2 nucleoprotein, using both human and pet sera, allowed the identification of the most antigenic region in the C-terminus domain of the protein, which was used to develop an experimental double antigen-based ELISA. A panel of pre-pandemic sera and sera of animals immunized against (or naturally infected with) related coronaviruses was used to assess assay specificity at 99.5%. Positive sera belonging to animals housed with COVID-19 patients were confirmed with the experimental double-antigen ELISA using Plaque Reduction Neutralization test (PRNT) test as gold standard. The availability of a serological assay that targets a highly specific viral antigen represents a valuable tool for multispecies monitoring of Coronavirus Disease 2019 (COVID-19) infection in susceptible animals. Highlights: Specific immunoresponse to SARS-CoV-2 in cats and dogs housed with COVID-19 patients. C-terminal domain of SARS-CoV-2 Nucleoprotein contains the immunodominant region Double-antigen ELISA for multispecies antibody detection against SARS-CoV-2 using Np antigen